2005
DOI: 10.1523/jneurosci.3073-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Protein Synthesis and Degradation Are Necessary for Efficient Growth Cone Regeneration

Abstract: Axonal regeneration can occur within hours of injury, the first step being the formation of a new growth cone. For sensory and retinal axons, regenerative ability in vivo correlates with the potential to form a new growth cone after axotomy in vitro. We show that this ability to regenerate a new growth cone depends on local protein synthesis and degradation within the axon. Axotomy in vitro leads to a fourfold to sixfold increase in 3 H-leucine incorporation in both neurones and axons, starting within 10 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
330
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(353 citation statements)
references
References 56 publications
12
330
1
5
Order By: Relevance
“…An increasing body of evidence indicates that DRG axons contain mRNA and that these axons are translationally competent (Zheng et al, 2001;Verma et al, 2005;Willis et al, 2005). In this study, we have shown that DRG and TG neurons express the RNA binding and transport proteins stau and FMRP and that these proteins localize to DRG axons.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…An increasing body of evidence indicates that DRG axons contain mRNA and that these axons are translationally competent (Zheng et al, 2001;Verma et al, 2005;Willis et al, 2005). In this study, we have shown that DRG and TG neurons express the RNA binding and transport proteins stau and FMRP and that these proteins localize to DRG axons.…”
Section: Discussionmentioning
confidence: 52%
“…There is now compelling evidence that translation occurs in axons (Koenig, 1967;Nixon, 1980;Koenig, 1991;Eng et al, 1999;Brittis et al, 2002;Piper and Holt, 2004), as mRNA and translational machinery have been localized to CNS (Tiedge et al, 1993;Aronov et al, 2001;Brittis et al, 2002), sympathetic (Olink-Coux andHollenbeck, 1996;Eng et al, 1999) and sensory (Zheng et al, 2001;Li et al, 2004a;Verma et al, 2005;Willis et al, 2005) axons. Moreover, an emerging physiological role for local translation in axons has been described for growth cone guidance and collapse (Zheng et al, 2001;Li et al, 2004a;Verma et al, 2005;Wu et al, 2005).Primary sensory neurons of the dorsal root ganglion (DRG) and trigeminal ganglion (TG) have among the longest axons of the entire neuraxis (greater than one meter for some human DRG neurons). Given the relatively long time interval required for axonal transport of proteins to occur in these neurons following somal synthesis, it would be advantageous if regulable, ondemand protein synthesis would occur at distal sites (for review see: Alvarez et al, 2000;Alvarez, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of the nervous system, guided axon growth requires intra-axonal mRNA translation, and it is thus not surprising that local protein synthesis is also crucial for axon regeneration. The formation of a new growth cone after axotomy of developing axons in vitro requires both local protein synthesis and degradation [30], and upon injury of mature axons, mRNAs and protein synthesis machinery are rapidly recruited into axons and intraaxonal translation is upregulated or re-activated within these mature axons [31][32][33][34]. Locally synthesized proteins are required for communication from the injured axons to their soma and likely participate in the formation of the growth bulb at the site of injury [35,36].…”
Section: Regeneration After Nerve Injurymentioning
confidence: 99%
“…54,55 The application of the p38 inhibitor significantly eliminated the growth cone formation and axon regeneration in the cultured DRG neurons. 56 These observations indicate an evolutionarily conserved role of the MAP synaptic branch somehow controls the intrinsic growth state of injured neurons and has an inhibitory effect on distal axon regeneration.…”
Section: Model In the Study Of Axon Regenerationmentioning
confidence: 94%